2018
DOI: 10.1371/journal.pone.0196838
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of knee extensor rate of velocity and power development in older adults using the isotonic mode on a Biodex System 3 dynamometer

Abstract: Isotonic testing and measures of rapid power production are emerging as functionally relevant test methods for detection of muscle aging. Our objective was to assess reliability of rapid velocity and power measures in older adults using the isotonic mode of an isokinetic dynamometer. Sixty-three participants (aged 65 to 82 years) underwent a test-retest protocol with one week time interval. Isotonic knee extension tests were performed at four different loads: 0%, 25%, 50% and 75% of maximal isometric strength.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
7
34
0
1
Order By: Relevance
“…Additionally, the rate of velocity development (RVD in°/s 2 ) at each resistance was calculated (Van Driessche et al, 2018b). Test-retest reliability in our lab shows an ICC ranging from 0.94 to 0.97 and CV% of 7.8 for the isometric tests (Van Roie et al, 2017;Van Driessche et al, 2018a). Reliability for pP, pV and RVD obtained from isotonic tests was also excellent with an ICC ranging from 0.85 to 0.98 for and CV% ranging from 3 to 9 (Van Driessche et al, 2018b).…”
Section: Force-velocity Characteristicsmentioning
confidence: 72%
See 1 more Smart Citation
“…Additionally, the rate of velocity development (RVD in°/s 2 ) at each resistance was calculated (Van Driessche et al, 2018b). Test-retest reliability in our lab shows an ICC ranging from 0.94 to 0.97 and CV% of 7.8 for the isometric tests (Van Roie et al, 2017;Van Driessche et al, 2018a). Reliability for pP, pV and RVD obtained from isotonic tests was also excellent with an ICC ranging from 0.85 to 0.98 for and CV% ranging from 3 to 9 (Van Driessche et al, 2018b).…”
Section: Force-velocity Characteristicsmentioning
confidence: 72%
“…Torque and velocity of the knee extensors were obtained using a Biodex System 4 Pro® isokinetic dynamometer (Biodex Medical Systems, Shirley, USA; Fig. 1), in accordance with procedures used in previous studies (Van Roie et al, 2011;Van Driessche et al, 2018a).…”
Section: Force-velocity Characteristicsmentioning
confidence: 99%
“…Sample size estimation was made using a web-based sample size calculator ( https://wnarifin.github.io/ssc/ssicc.html ) and methods from Walter et al [ 14 ]. A previous reliability study testing muscle power in older adults [ 9 ] reported an intraclass correlation coefficient (ICC) of 0.96. Using the minimum acceptable reliability of 0.75 [ 15 ], α = 0.05, 80% power, and two repetitions/raters per participant would require a sample size of at least 10 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to perform all contractions “as hard and as fast as possible,” and motivation was provided throughout the trial. Maximal voluntary isometric contraction (MVIC) of the knee extensors (KE) and knee flexors (KF) were measured at a knee angle of 90 degrees [ 9 ]. Each trial consisted of KE MVIC, and a brief rest followed by KF MVIC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation